Armas de doble filo : el humor en The Fat Black Woman's Poems y Lazy Thoughts of a Lazy Woman, de Grace Nichols - Galettini, Azucena (2020)
El segundo y tercer poemario (The Fat Black Woman's Poems (1984) y Lazy Thoughts of a Lazy Woman (1989), respectivamente) de Grace Nichols, autora guyanesa residente en el Reino Unido desde 1977, se encuentran hermanados por el uso del humor. Criticada por valerse de este recurso, visto como un exceso de liviandad para tratar temas complejos como el pasado de esclavitud, la dura vida del inmigrante caribeño o la sexualidad femenina, Nichols revindica su utilización en tanto implica su adscripción a la tradición antillana. En el presente trabajo, mediante el análisis de cuatro poemas (dos de cada libro), se explora cómo opera el humor en ambas obras y qué simplificaciones conlleva, poniendo especial énfasis en cómo la aparente liviandad que aporta es, en tanto tradición caribeña, otro modo de resistencia.
The second and third poetry collection (The Fat Black Woman's Poems (1984) y Lazy Thoughts of a Lazy Woman (1989), respectively) by Grace Nichols, Guyanese author living in the United Kingdom since 1977, are related due to the use of humor. Criticized for utilizing this resource, seen as excess of lightness when addressing complex themes such as slavery, the harsh life of the Caribbean immigrant, or female sexuality, Nichols reclaims humor as a way of ascribing herself to Antillean tradition. In the current essay, we will explore through the analysis of four poems (two from each book) how humor operates in both collections and which simplifications it entails, emphasizing how the apparent lightness it gives is, seen as part of Caribbean tradition, another way of resistance.
Keywords: Humor; Poesía caribeña; Desborde; Quiebre; Grace nichols; Humor; Caribbean poetry; Overflow; Breaks; Grace Nichols